A method for preparing biodegradable heat shrinkable film

By optimizing the tensile ratio and cold setting treatment, a biodegradable heat shrink film with high equalization heat shrinkage rate and tear strength was prepared, which solved the problem of poor vertical and horizontal balance of the heat shrink film in the prior art, and achieved better packaging performance and optical performance.

CN115674626BActive Publication Date: 2025-03-25KINGFA SCI & TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211242506.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-11
Publication Date
2025-03-25
Estimated Expiration
2042-10-11

AI Technical Summary

Technical Problem

The existing biodegradable heat shrink films have poor balance in terms of longitudinal and transverse heat shrinkage and tear strength, and it is difficult to meet the requirements of high equalization shrinkage and complete biodegradation at the same time.

Method used

By optimizing the longitudinal stretch ratio, transverse stretch ratio and tensile aspect ratio, and cold-shaped treatment after stretching, a biodegradable heat shrink film with balanced heat shrinkage and tear strength was prepared.

Benefits of technology

The high heat shrinkage rate and balanced tear strength of the biodegradable heat shrink film in both vertical and horizontal directions are achieved, which improves the packaging shrinkage protection and tear resistance, while optimizing the light transmittance and reducing haze.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a method for preparing a biodegradable heat shrinkable film. The preparation method comprises the following steps: heating the biodegradable heat shrinkable film material to a molten state, casting and cooling; then performing two stretching treatments in sequence to obtain a biodegradable heat shrinkable film; the stretching treatment is preheating, transverse stretching or longitudinal stretching, and cold setting treatment; by weight, the biodegradable heat shrinkable film material comprises: 30 to 95 parts of aliphatic biodegradable copolyester or aliphatic-aromatic biodegradable copolyester, 5 to 70 parts of polylactic acid; the longitudinal stretching ratio is (1 to 6): 1, the transverse stretching ratio is (3 to 10): 1, and the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1: (1 to 10); the temperature of the cold setting treatment is 1 to 25 ° C. The biodegradable heat shrinkable film not only maintains a high heat shrinkage rate and tear strength in the longitudinal and transverse directions, but also has a more balanced heat shrinkage rate and tear strength in the longitudinal and transverse directions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of completely biodegradable materials, and more specifically, relates to a method for preparing a biodegradable heat shrinkable film. Background Art

[0002] Heat shrink films are widely used in the packaging of beverages, foods, industrial products, etc. (heat shrinks and wraps tightly to prevent the contents of the package from detaching from each other, as well as to cover and protect the contents), as well as plastic bottle labels and other outer packaging purposes. Existing commonly used plastic heat shrink films are mainly made of traditional petroleum-based plastics such as PE, PP, PVC, PET, PETG, etc., which are not biodegradable and are used in large quantities as packaging for daily necessities and industrial products. They are difficult to handle in the natural environment for a long time after being discarded, and there are problems of large amounts of residual pollution. In addition, due to the need for packaging effects, the thickness of traditional plastic shrink films such as PE is relatively thick, and it is difficult to separate them from the contents or containers such as bottles and cans after being attached. The recycling and reuse methods are complicated and the cost is too high, which also makes it difficult to promote the recycling plan of heat shrink films.

[0003] Patent CN 102712766 B discloses a method for producing heat shrinkable films using a blown film preparation process of a biodegradable aliphatic / aromatic copolyester (preferably PBST and PBAT) / polylactic acid composition. Since the blowing ratio of the blown film method is limited by the processability of the film bubble support, the heat shrinkage rate of the blown film heat shrinkable film has a large anisotropy in the longitudinal and transverse directions, and the adjustment flexibility is also extremely low. In addition, the blown film method has a low transparency caused by low product cooling efficiency, and the visibility of the package contents is greatly reduced.

[0004] Patent CN 103625061 A adopts a three-layer co-extrusion method to prepare a degradable heat shrinkable film, wherein the three layers are mainly made of polylactic acid, and the proportion of other materials is relatively low. This material formula will result in the shrinkage film having high stiffness and brittleness, but insufficient flexibility, and it is difficult to meet the shrinkage packaging requirements of bulk products; the three-layer co-extrusion process also has the problems of high equipment investment, complex product processing, and the shrinkage rate, transparency and other physical properties are greatly affected by the thickness ratio of each of the three layers; in addition, the patent only involves the transverse stretching process, and the prepared degradable heat shrinkable film also has the problem of large differences in shrinkage rate in the longitudinal and transverse directions and difficulty in regulation.

[0005] Patent CN 106519599 B uses polyethylene terephthalate and other fillers and additives as the main material formula to prepare a heat shrink film by a biaxial stretching process. The formula materials in this patent are all non-biodegradable materials, which do not have environmental protection and degradation functions. After being discarded, there are environmental problems such as difficulty in landfill and recycling, causing white pollution, etc.

[0006] In summary, existing products all have various defects, and it is difficult to simultaneously meet the requirements of high balanced shrinkage rate and complete biodegradability. Existing patents for biodegradable heat shrinkable films also have defects in materials and preparation methods. It is necessary to develop a new preparation method for biodegradable shrinkage film materials. Summary of the invention

[0007] In view of the above-mentioned existing technical problems, the primary purpose of the present invention is to provide a method for preparing a biodegradable heat shrinkable film. By optimizing the longitudinal stretching ratio and the transverse stretching ratio and the stretching aspect ratio (the ratio of the longitudinal stretching ratio to the transverse stretching ratio) and the cold setting treatment after stretching, the prepared biodegradable heat shrinkable film not only maintains a high heat shrinkage rate and tear strength in the longitudinal and transverse directions, but also has a more balanced heat shrinkage rate and tear strength in the longitudinal and transverse directions.

[0008] The second object of the present invention is to provide a biodegradable heat shrinkable film prepared by the above preparation method.

[0009] The third object of the present invention is to provide the use of the above-mentioned biodegradable heat shrinkable film in the preparation of shrink packaging products.

[0010] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0011] A method for preparing a biodegradable heat shrinkable film comprises the following steps:

[0012] S1. The biodegradable heat shrinkable film material is heated into an extruder until it is molten, and then cast onto a chilled roller and cooled to form a cast sheet;

[0013] S2. Preheating the cast sheet in S1, stretching it longitudinally, and then cold-setting it, then preheating the cast sheet after cold-setting it, stretching it transversely, and cold-setting it to obtain the biodegradable heat shrinkable film; or

[0014] After preheating the casting sheet in S1, stretching it transversely, and then cold setting it, then preheating the casting sheet after cold setting, stretching it longitudinally, and cold setting it to obtain the biodegradable heat shrinkable film;

[0015] The biodegradable heat shrinkable film material comprises, by weight: 30 to 95 parts of biodegradable copolyester and 5 to 70 parts of polylactic acid; the biodegradable copolyester is an aliphatic biodegradable copolyester or an aliphatic-aromatic biodegradable copolyester; the longitudinal stretching ratio is (1 to 6):1, the transverse stretching ratio is (3 to 10):1, and the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1:(1 to 10); the temperature of the cold setting treatment is 1 to 25°C.

[0016] During the casting process, the degradation film flows down from the die and then passes through the speed difference of all subsequent rollers from traction to transition to winding to reach the required thickness. This process will achieve a certain degree of longitudinal stretching, that is, a certain longitudinal stretching ratio. After preheating, it is stretched in both the transverse and longitudinal directions. The molecular chains of the film material undergo a more complex cooling crystallization, crystal zone slip, and longitudinal and transverse bidirectional preferential arrangement and orientation of the molecular chains. In the end, it will show different levels and balance of thermal shrinkage rates, as well as isotropic changes in mechanical properties including tear strength. A small stretch ratio is manifested as a small shrinkage rate, and a large stretch ratio is the opposite. It is generally believed that the closer the stretching aspect ratio is to 1, the more uniform the longitudinal and transverse orientation of the film material will be. However, the inventors have found through long-term research that for biodegradable materials of a specific system (such as biodegradable materials of the polybutylene adipate terephthalate / polylactic acid (PBAT / PLA) system), due to the presence of polylactic acid in the biodegradable material, the unique molecular chain structure and crystal arrangement of polylactic acid have a decisive influence on the thermal shrinkage rate (both longitudinally and transversely), and the conventional stretching ratio and stretching aspect ratio cannot achieve high thermal shrinkage and balance of the film material.

[0017] The inventors have changed the direction and degree of molecular chain orientation in the biodegradable material film of a specific system by optimizing the specific longitudinal stretching ratio, transverse stretching ratio and the range of the stretching aspect ratio, and improved isotropy, so that the longitudinal and transverse directions not only have higher thermal shrinkage and tear strength, but also have more balanced thermal shrinkage and tear strength. At the same time, the inventors have found through long-term research that the biodegradable materials of a specific system will lead to a tendency of deorientation after being stretched, and due to the specific ester bonds and some special benzene ring structures in the biodegradable materials, the degree of molecular deorientation is particularly obvious, and the biodegradable shrink film after the heat setting treatment almost loses its thermal shrinkage. Based on this, the inventors cold-set the heat shrink film after the stretching treatment, and the cold setting treatment after the stretching reduces the deorientation tendency of the biodegradable heat shrink film in the longitudinal and transverse directions, so that the thermal shrinkage rate of the prepared biodegradable heat shrink film does not decrease, and maintains a high thermal shrinkage rate.

[0018] Preferably, the biodegradable copolyester is selected from one or more of polybutylene adipate terephthalate, polybutylene sebacate terephthalate, polyhydroxyalkanoate or polybutylene succinate, and more preferably polybutylene adipate terephthalate.

[0019] Preferably, the longitudinal stretching ratio is (2-4):1, the transverse stretching ratio is (4-8):1, and the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1:(2-4).

[0020] Preferably, the longitudinal stretching ratio is (2-3):1, the transverse stretching ratio is (6-8):1, and the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1:(2-3).

[0021] Most preferably, the longitudinal stretching ratio is 2: 1, the transverse stretching ratio is 6: 1, and the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1: 3. Under this preferred range, the biodegradable heat shrinkable film prepared by the present invention has a higher and more balanced heat shrinkage rate and tear strength.

[0022] Further preferably, when the preferred temperature of the cold setting treatment is 10-14° C., the biodegradable heat shrinkable film prepared by the present invention can obtain a higher heat shrinkage rate.

[0023] Preferably, the cold setting treatment uses 4 to 6 groups of cooling setting rollers connected closely together, preferably 6 groups; the front and rear distance of all the cold setting rollers is 4 to 10 meters, preferably 6 to 10 meters.

[0024] Preferably, the temperature of the longitudinal stretching is 50-80°C; and the temperature of the transverse stretching is 70-110°C.

[0025] Preferably, the cooling temperature of the chilled roller is 1-20°C. The molecular chains of biodegradable polyester materials (such as polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS) and polylactic acid (PLA)) are relatively long, and there are steric functional groups such as benzene rings, ester bonds, and hydroxyl groups, and the regularity is poor. In the process of melt cooling and crystallization, there are slow crystallization speed, mixed crystal forms and uneven crystallinity. The inventor optimizes the cooling temperature of the chilled roller, so that the biodegradable heat shrinkable material is rapidly cooled at low temperatures in the last two chilled rollers under melt casting, so that the melt preferentially generates uniform fine crystals and uniform γ crystals during the cooling process, and then reaches a regular and uniform degree of crystallization after uniform growth, which can significantly optimize and improve the light transmittance of the biodegradable heat shrinkable film, reduce the haze of the biodegradable heat shrinkable film; and improve the mechanical strength.

[0026] Preferably, the chilled roller cooling can adopt double-pass chilled roller cooling, which has higher cooling efficiency, longer cooling time and better cooling effect, and can better improve the light transmittance of the biodegradable heat shrinkable film and reduce the haze.

[0027] Preferably, the preheating temperature is 40-80°C.

[0028] Preferably, the biodegradable heat shrinkable film material further contains, by weight: 0.1 to 20 parts of filler and 0.001 to 20 parts of auxiliary agent.

[0029] Preferably, the filler includes organic filler and / or inorganic filler; the organic filler is selected from one or more of starch, natural fiber, straw, wood powder or bamboo powder; the inorganic filler is selected from one or more of talc, montmorillonite, kaolin, chalk, calcium carbonate, graphite, gypsum, conductive carbon black, calcium chloride, iron oxide, dolomite, silicon dioxide, wollastonite, titanium dioxide, silicate, mica, glass fiber or mineral fiber.

[0030] Preferably, the auxiliary agent is selected from one or more of lubricants, slip agents, anti-blocking agents, nucleating agents, surfactants, antistatic agents, pigments, anti-hydrolysis agents, anti-UV agents, antioxidants, chain extenders, cross-linking agents or anti-fogging agents.

[0031] Preferably, the biodegradable heat shrinkable film material can be put into a single-layer extruder, a double-layer co-extrusion extruder or a three-layer co-extrusion extruder in any proportion of a single-layer, double-layer or three-layer structure.

[0032] Furthermore, the present invention also protects the biodegradable heat shrinkable film prepared by the above preparation method.

[0033] Preferably, the average thickness of the biodegradable heat shrinkable film is 20 μm to 80 μm.

[0034] Furthermore, the present invention also provides the use of the above-mentioned biodegradable heat shrinkable film in the preparation of shrink packaging products. Specifically, the products can be beverages, mineral water, alcohol, resin packaging, toys, tableware, food, health products, paper products, picture frame products, books and periodicals, audio-visual products, stationery, handicrafts, building materials, cosmetics, electronic products, daily chemicals and the like.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention optimizes the specific longitudinal stretching ratio, transverse stretching ratio, stretching aspect ratio range and cold setting treatment after stretching, so that the heat shrinkage rate of the prepared biodegradable heat shrinkable film in both the longitudinal and transverse directions is maintained at more than 55%, and the heat shrinkage rate and tear strength in the longitudinal and transverse directions are more balanced, thereby improving the actual packaging shrinkage protection and tear resistance effect of the biodegradable heat shrinkable film.

[0037] (2) The present invention optimizes the cooling temperature of the chill roller so that the biodegradable heat shrinkable material is rapidly cooled at a low temperature by the chill roller after melt casting, thereby significantly optimizing and improving the light transmittance of the biodegradable heat shrinkable film and reducing the haze of the biodegradable heat shrinkable film. DETAILED DESCRIPTION

[0038] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0039] Examples and Comparative Examples Raw Materials Description:

[0040] PLA: 4032D, Natureworks, USA;

[0041] PBAT: A400, Kingfa Science & Technology Co., Ltd.;

[0042] Filler: talc, 3000 mesh, from commercial sources;

[0043] Additives: lubricant, commercially available;

[0044] Antioxidant, 1010, from commercial sources;

[0045] The chain extender, glycidyl methacrylate, was commercially available.

[0046] The testing methods of the specific parameters in the following embodiments are as follows:

[0047] Average thickness (μm): tested using GB / T 6672-2001 test method.

[0048] Tear strength (mN): tested using GB / T 16578.2-2009 test method.

[0049] Thermal shrinkage (120°C, 10s): tested using the GB / T 34848-2017 test method.

[0050] Light transmittance: tested using GB / T 2410-2008 test method.

[0051] Haze: Tested using GB / T 2410-2008 test method.

[0052] Example 1 Preparation of biodegradable heat shrinkable film

[0053] The biodegradable heat shrinkable film adopts an AB double-layer co-extrusion structure. Calculated by weight, the A layer formula is: 50 parts of PLA, 50 parts of PBAT, 5 parts of talc, 0.5 parts of lubricant, 0.2 parts of antioxidant, and 0.1 parts of chain extender; the B layer formula is: 70 parts of PLA, 30 parts of PBAT, 5 parts of talc, 0.5 parts of lubricant, 0.2 parts of antioxidant, and 0.1 parts of chain extender.

[0054] The preparation method of the biodegradable heat shrinkable film comprises the following steps:

[0055] (1) After the A layer formulation components are uniformly mixed, they are put into a twin-screw extruder, extruded at 140-190° C., and granulated to obtain a biodegradable heat shrinkable film material A; after the B layer formulation components are uniformly mixed, they are put into a twin-screw extruder, extruded at 140-190° C., and granulated to obtain a biodegradable heat shrinkable film material B;

[0056] (2) putting the biodegradable heat shrinkable film material A and the biodegradable heat shrinkable film material B into corresponding single-screw extruders, plasticizing and melting at 120° C. to 180° C., and entering the die through a filter and a melt metering pump;

[0057] (3) The melt is melted and plasticized, and then converged through the die head and cast onto a chilled roller for cooling. The cooling temperature of the double-pass chilled roller is 12°C, and the cast sheet is formed by rotation;

[0058] (4) The casting is preheated, longitudinally stretched, and cold-set in sequence by different pulling rollers of the longitudinal stretching unit, wherein the preheating temperature is 60°C; the longitudinal stretching is achieved by 4 groups of stretching rollers, the longitudinal stretching temperature is 70°C, and the longitudinal stretching ratio is 2:1; and the cold setting is performed by 6 groups of cooling setting rollers, and the cold setting temperature is 12°C.

[0059] (5) After longitudinal stretching, the cast sheet enters a transverse stretching unit for preheating, transverse stretching, and cold setting treatment, and then the prepared biodegradable heat shrinkable film is cut and rolled to obtain a heat shrinkable film with a thickness of 45 μm; wherein the preheating temperature is 60° C.; the transverse stretching temperature is 90° C., the transverse stretching ratio is 6:1; and the cold setting temperature is 12° C.

[0060] Example 2 Preparation of biodegradable heat shrinkable film

[0061] The difference between this embodiment and embodiment 1 is that the longitudinal stretching ratio is 3:1; the transverse stretching ratio is 4:1; and the stretching aspect ratio is 1:1.33.

[0062] Example 3 Preparation of biodegradable heat shrinkable film

[0063] The difference between this embodiment and embodiment 1 is that the longitudinal stretching ratio is 4:1; the transverse stretching ratio is 7:1; and the stretching aspect ratio is 1:1.75.

[0064] Example 4 Preparation of biodegradable heat shrinkable film

[0065] The difference between this embodiment and embodiment 1 is that the longitudinal stretching ratio is 6:1; the transverse stretching ratio is 6:1; and the stretching aspect ratio is 1:1.

[0066] Example 5 Preparation of biodegradable heat shrinkable film

[0067] The difference between this embodiment and embodiment 1 is that the longitudinal stretching ratio is 1:1; the transverse stretching ratio is 10:1; and the stretching aspect ratio is 1:10.

[0068] Example 6 Preparation of biodegradable heat shrinkable film

[0069] The difference between this embodiment and embodiment 1 is that the longitudinal stretching ratio is 3:1; the transverse stretching ratio is 3:1; and the stretching aspect ratio is 1:1.

[0070] Example 7 Preparation of biodegradable heat shrinkable film

[0071] The difference between this embodiment and embodiment 1 is that the longitudinal stretching ratio is 6:1; the transverse stretching ratio is 10:1; and the stretching aspect ratio is 1:1.67.

[0072] Example 8 Preparation of biodegradable heat shrinkable film

[0073] The difference between this embodiment and embodiment 1 is that the cold setting treatment temperature during longitudinal stretching is 1°C, and the cold setting treatment temperature during transverse stretching is 1°C.

[0074] Example 9 Preparation of biodegradable heat shrinkable film

[0075] The difference between this embodiment and embodiment 1 is that the cold setting treatment temperature during longitudinal stretching is 25°C, and the cold setting treatment temperature during transverse stretching is 25°C.

[0076] Example 10 Preparation of biodegradable heat shrinkable film

[0077] The difference between this embodiment and embodiment 1 is that the mass fraction of the A layer formula is 100% (ie, it only contains the A layer components).

[0078] Example 11 Preparation of biodegradable heat shrinkable film

[0079] The difference between this embodiment and embodiment 1 is that the mass fraction of the B layer formula is 100% (ie, it only contains the B layer components).

[0080] Example 12 Preparation of biodegradable heat shrinkable film

[0081] The difference between this embodiment and embodiment 1 is that: the formulation of layer A is: 30 parts of PLA, 70 parts of PBAT, 5 parts of talcum powder, 0.5 parts of lubricant, 0.2 parts of antioxidant, and 0.1 parts of chain extender; the formulation of layer B is the same.

[0082] Example 13 Preparation of biodegradable heat shrinkable film

[0083] The difference between this embodiment and embodiment 1 is that: the formula of layer A is: 5 parts of PLA, 95 parts of PBAT, 5 parts of talcum powder, 0.5 parts of lubricant, 0.2 parts of antioxidant, and 0.1 parts of chain extender; the formula of layer B is the same.

[0084] Examples 14-15 Optimization of forced cooling by double-pass chilled rollers

[0085] The difference between Example 14 and Example 1 is that the cooling temperature of the double-pass chilled roller is 25°C.

[0086] The difference between Example 15 and Example 1 is that the cooling temperature of the double-pass chilled roller is 40°C.

[0087] The various properties of the biodegradable heat shrinkable films prepared in the above Examples 1 to 15 are shown in Table 1 below:

[0088] Table 1

[0089]

[0090] As shown in Table 1 above, Examples 1 to 7 show that compared with Examples 2 to 7 (stretching aspect ratio outside the range of 1:(2 to 4)), the biodegradable heat shrinkage film prepared in Example 1 (stretching aspect ratio 1:3) has a longitudinal and transverse heat shrinkage rate greater than 70%, which not only has a high heat shrinkage rate, but also is very balanced. This is because in the biaxial stretching process, the melt is cast onto the chilled roller and in the subsequent traction process, which itself has a certain longitudinal orientation. Therefore, a certain stretching aspect ratio must be met in the longitudinal stretching and transverse stretching processes to achieve a balanced and high shrinkage rate. Otherwise, anisotropy is easily caused, resulting in an excessively strong orientation in one direction, so that a certain degree of molecular chain relaxation occurs in the other perpendicular direction, resulting in a deviation in the shrinkage balance and a low overall value.

[0091] Examples 4 and 6 are the cases where the longitudinal stretching ratio and the transverse stretching ratio are the same under the stretching aspect ratio of 1:1, and Example 5 is the case where the stretching aspect ratio is lower. By comparison, it can be seen that when the longitudinal stretching ratio and the transverse stretching ratio are the same, the longitudinal shrinkage rate will be significantly higher than the transverse shrinkage rate.

[0092] It can be seen from the test results of Examples 8 and 9 that when the cold setting treatment temperature of the longitudinal stretching and the transverse stretching is between 1 and 25° C., the heat shrinkage rate of the prepared biodegradable heat shrinkable film is above 55%.

[0093] It can be seen from Examples 10 to 13 that in the biodegradable heat shrinkable film material, when the biodegradable copolyester is in the range of 30 to 95 parts and the polylactic acid is in the range of 5 to 70 parts, the single-layer biodegradable heat shrinkable film can also achieve a balanced high heat shrinkage rate.

[0094] As can be seen from Table 1 above, the longitudinal and transverse heat shrinkage rates of the biodegradable heat shrinkable films prepared in Examples 1 to 15 of the present application are not only greater than 55%, but also the longitudinal tear strength is 1200 to 2500 mN, the transverse tear strength can be maintained at 3000 to 4200 mN; the light transmittance is ≥ 65%; and the haze is < 32. Further preferably, the biodegradable heat shrinkable films prepared in Examples 1 to 13 have more balanced longitudinal and transverse tear strengths, the longitudinal tear strength can be maintained at 1900 to 2500 mN, and the transverse tear strength can be maintained at 3800 to 4200 mN; have better optical properties, light transmittance is ≥ 80%; and the haze is < 5.5.

[0095] Comparative Examples 1-2 Preparation of Biodegradable Heat Shrinkable Film by Film Blowing

[0096] Comparative Example 1: The formula in Example 1 was added into a single screw machine for melting and ripening, and a heat shrinkable film was formed by an upward blowing film blowing process, wherein the extrusion temperature was 130-170°C, the die head temperature was 150°C, and the blowing ratio was 3:1.

[0097] Comparative Example 2: The formula in Example 10 was added into a single screw machine for melting and ripening, and a heat shrinkable film was formed by an upward blowing film blowing process, wherein the extrusion temperature was 130-170°C, the die head temperature was 150°C, and the blowing ratio was 3:1.

[0098] Comparative Examples 1 and 2 were used to prepare biodegradable heat shrinkable films with a nominal thickness of 45 μm. The various properties of the biodegradable heat shrinkable films tested are shown in Table 2 below:

[0099] Table 2

[0100]

[0101] It can be seen from Table 2 above that the biodegradable shrink films of the same formulation prepared by the film blowing method in Comparative Examples 1 and 2 have lower longitudinal tear strength and optical properties than the biodegradable shrink films prepared by the biaxial stretching method in Example 1 and Example 10, respectively, due to insufficient cooling efficiency determined by the cooling method and the limitation of the inflation process of the film blowing molding on the orientation degree in the longitudinal and transverse directions.

[0102] The biodegradable heat shrinkable film prepared by the biaxial stretching method in Example 1 and Example 10 not only has excellent light transmittance and extremely low haze, showing good optical properties; but also has excellent longitudinal and transverse heat shrinkage rates, and its balance is also relatively excellent, especially the transverse heat shrinkage rate in Comparative Examples 1 to 2 is far different from the transverse heat shrinkage rate in Example 1 and Example 10.

[0103] Comparative Examples 3 to 7 Optimization of different longitudinal stretching ratios, transverse stretching ratios and stretching aspect ratios

[0104] The difference between Comparative Example 3 and Example 1 is that the longitudinal stretching ratio is 2:1; the transverse stretching ratio is 2:1; and the stretching aspect ratio is 1:1.

[0105] The difference between Comparative Example 4 and Example 1 is that the longitudinal stretching ratio is 8:1; the transverse stretching ratio is 8:1; and the stretching aspect ratio is 1:1.

[0106] The difference between Comparative Example 5 and Example 1 is that the longitudinal stretching ratio is 3:1; the transverse stretching ratio is 15:1; and the stretching aspect ratio is 1:5.

[0107] The difference between Comparative Example 6 and Example 1 is that the longitudinal stretching ratio is 15:1; the transverse stretching ratio is 3:1; and the stretching aspect ratio is 5:1.

[0108] The difference between Comparative Example 7 and Example 1 is that the longitudinal stretching ratio is 6:1; the transverse stretching ratio is 3:1; and the stretching aspect ratio is 2:1.

[0109] Comparative Examples 3 to 7 were used to prepare biodegradable heat shrinkable films with a nominal thickness of 45 μm. The properties of the films tested are shown in Table 3 below:

[0110] Table 3

[0111]

[0112] It can be seen from Table 3 above that, compared with Comparative Examples 3 to 7, the heat shrinkage rate of the biodegradable heat shrinkable film prepared in Example 1 in the longitudinal and transverse directions can reach more than 55%, and has excellent shrink wrap protection; in addition, the heat shrinkage rate is also greatly affected by the stretching aspect ratio. When the cast melt is cooled to the winding process, that is, when a certain longitudinal stretching ratio is obtained, the balance (isotropy) of the heat shrinkage rate of the biodegradable heat shrinkable film prepared in Example 1 (stretching aspect ratio is 1:3) is significantly better than that of the biodegradable heat shrinkable films prepared in Comparative Examples 3 to 7 (stretching aspect ratios are 1:5, 1:1, 5:1 and 2:1, respectively).

[0113] In addition, the inventors found that when the stretching aspect ratio coefficient is too small or too large, that is, when the longitudinal stretch ratio is too large or the transverse stretch ratio is too large, the shrinkage rate in the other direction will show a downward trend (such as Comparative Examples 6 and 7). The main reasons are: first, there is a certain initial longitudinal stretching behavior in the entire casting process, and the superimposed longitudinal stretching ratio will cause the actual longitudinal stretching ratio to be too large. Secondly, and more importantly, it is the stretching orientation process of the molecular chain of the biodegradable polyester material. When the unidirectional orientation is too large, it will cause the molecular chain to relax in the other direction, thereby producing de-orientation, thereby causing the thermal shrinkage rate in the other direction to decrease.

[0114] The above data show that the longitudinal stretching ratio, transverse stretching ratio and stretching aspect ratio all need to be controlled within an appropriate range in order to achieve high thermal shrinkage and balance in the longitudinal and transverse directions.

[0115] Comparative Examples 8 to 10 Optimization of different shaping methods after stretching

[0116] The difference between Comparative Example 8 and Example 1 is that in step (3) and step (4), no cold setting treatment is performed after longitudinal stretching and transverse stretching.

[0117] The difference between Comparative Example 9 and Example 1 is that the temperature of the cold setting treatment is 30°C.

[0118] The difference between Comparative Example 10 and Example 1 is that in steps (3) and (4), after longitudinal stretching and transverse stretching, 6 sets of heat setting rollers are used for treatment, and the setting temperature is 45°C.

[0119] Comparative Examples 8 to 10 were used to prepare biodegradable heat shrinkable films with a nominal thickness of 45 μm. The properties of the films tested are shown in Table 4 below:

[0120] Table 4

[0121]

[0122] It can be seen from Table 4 above that, whether it is longitudinal stretching or transverse stretching, active forced cooling crystallization and shaping after molecular chain orientation helps to avoid deorientation. In Comparative Example 8, no cold setting treatment was performed after longitudinal stretching and transverse stretching, and the molecular chain deorientation was obvious. The longitudinal and transverse heat shrinkage rates of the prepared biodegradable heat shrinkable film were low. The bidirectional heat shrinkage rate of the biodegradable heat shrinkable film prepared in Example 1 (the temperature of the cold setting treatment was 12°C) was also significantly better than that of the biodegradable heat shrinkable film of Comparative Example 9 (the cooling temperature was 30°C). However, the use of heat setting process in Comparative Example 10 obviously caused the relaxation of the molecular chain of the biodegradable heat shrinkable film, and the deorientation was obvious, and the heat shrinkage rate was almost lost.

[0123] Comparative Examples 11-13 Preparation of biodegradable heat shrinkable films made of different biodegradable materials

[0124] The difference between Comparative Example 11 and Example 10 is that: A layer formula: 2 parts of PLA, 98 parts of PBAT, 5 parts of talc, 0.5 parts of lubricant, 0.2 parts of antioxidant, and 0.1 parts of chain extender.

[0125] The difference between Comparative Example 12 and Example 10 is that PPC (polymethyl ethylene carbonate, commercial film grade) is 95 parts, PLA is 5 parts, talc is 5 parts, lubricant is 0.5 parts, antioxidant is 0.2 parts, and chain extender is 0.1 parts.

[0126] The difference between Comparative Example 13 and Example 10 is that: PET (polyethylene terephthalate, commercially available film grade) is 95 parts, PLA is 5 parts, talcum powder is 5 parts, lubricant is 0.5 parts, antioxidant is 0.2 parts, chain extender is 0.1 parts; melted at 220-270°C.

[0127] Comparative Examples 11 to 13 were used to prepare biodegradable heat shrinkable films with a nominal thickness of 45 μm. The properties of the films tested are shown in Table 5 below:

[0128] Table 5

[0129]

[0130] As can be seen from Table 5 above, the unique molecular chain structure and crystal arrangement of polylactic acid have an important influence on the heat shrinkage rate (both longitudinally and transversely), and the key indicators of the heat shrinkage rate of the biodegradable heat shrinkable film can be adjusted by optimizing the number of polylactic acid PLA in the formula. In Comparative Example 11, a single-layer, high-PBAT content heat shrinkable film was used. In terms of mechanical properties, although its flexibility is higher than that of Example 1, it has no heat shrinkage. In Comparative Examples 12 to 13, different polyester components did not show sufficient heat shrinkage under the conditions of the specific chilled roller temperature, cold setting treatment, stretching aspect ratio, and longitudinal and transverse stretching ratios in Example 1, and the light transmittance, haze and tear strength were also quite different from those in Example 1. The comprehensive performance effect of the biodegradable heat shrinkable film prepared in Comparative Examples 11 to 13 is much lower than that of Example 1.

[0131] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A method for preparing a biodegradable heat shrinkable film, characterized in that: The following steps are involved: S1. The biodegradable heat shrinkable film material is heated into an extruder until it is molten, and then cast onto a chilled roller and cooled to form a cast sheet; S2. The cast sheet of S1 is preheated, longitudinally stretched, and then cold-set, and then the cold-set cast sheet is preheated and transversely stretched, and cold-set to obtain the biodegradable heat shrinkable film; or After preheating the casting sheet in S1, stretching it transversely, and then cold setting it, then preheating the casting sheet after cold setting, stretching it longitudinally, and cold setting it to obtain the biodegradable heat shrinkable film; In terms of weight, the biodegradable heat shrinkable film material comprises: 30 to 95 parts of biodegradable copolyester and 5 to 70 parts of polylactic acid; The longitudinal stretching ratio is (1-6):1, the transverse stretching ratio is (3-10):1, and the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1:(1-10); the temperature of the cold setting treatment is 1-25°C; The biodegradable copolyester is selected from one or more of polybutylene adipate terephthalate, polybutylene sebacate terephthalate, polyhydroxyalkanoate or polybutylene succinate.

2. The preparation method according to claim 1, characterized in that: The longitudinal stretching ratio is (2-4):1, and the transverse stretching ratio is (4-8):1; the ratio of the longitudinal stretching ratio to the transverse stretching ratio is 1:(2-4).

3. The preparation method according to claim 1, characterized in that: The temperature of the cold setting treatment is 10-14°C.

4. The preparation method according to claim 1, characterized in that: The temperature of the longitudinal stretching is 50-80°C, and the temperature of the transverse stretching is 70-110°C.

5. The preparation method according to claim 1, characterized in that: The cooling temperature of the chilled roller is 1-20°C.

6. The preparation method according to claim 1, characterized in that: The biodegradable heat shrinkable film material further contains, by weight: 0.1 to 20 parts of filler and 0.001 to 20 parts of auxiliary agent.

7. The preparation method according to claim 6, characterized in that: The filler includes organic filler and / or inorganic filler; the organic filler is selected from one or more of starch, natural fiber, straw, wood powder or bamboo powder; the inorganic filler is selected from one or more of montmorillonite, kaolin, calcium carbonate, graphite, gypsum, conductive carbon black, calcium chloride, iron oxide, dolomite, silicon dioxide, titanium dioxide, silicate, mica, glass fiber or mineral fiber; the auxiliary agent is selected from one or more of lubricants, slip agents, anti-blocking agents, nucleating agents, surfactants, antistatic agents, pigments, anti-hydrolysis agents, anti-UV agents, antioxidants, chain extenders, cross-linking agents or anti-fogging agents.

8. The preparation method according to claim 7, characterized in that: The silicate is selected from one or more of talc and wollastonite.

9. The preparation method according to claim 7, characterized in that: The calcium carbonate is chalk.

10. The biodegradable heat shrinkable film prepared by the preparation method according to any one of claims 1 to 9.

11. Use of the biodegradable heat shrinkable film according to claim 10 in preparing shrink packaging products.

Citation Information

Patent Citations

  • Method for producing shrink films

    CN102712766B

  • Tape-casting environment-friendly degradable heat-shrink film and manufacturing method thereof

    CN103625061A

  • A kind of multipurpose heat shrinkable film with high stability and preparation method thereof

    CN106519599B

  • Polyester thermal contraction film with balanced thermal contraction performance and production method thereof

    CN101531079A

  • Thermoshrinkable polyester film and preparation method thereof

    CN102816417A